Tanggung Jawab Shopee Express atas Kehilangan Barang yang Dilakukan oleh Kurir Dihubungkan dengan Undang-Undang No 8 Tahun 1999 Tentang Perlindungan Konsumen - Jasmine Shafa Sabrina Darmawan; Liya Sukma Muliya (UNISBA Press, 2023)
Abstract. The field of transportation is a very vital activity in people's lives. Shopee Express is one of Shopee's innovations to develop its own logistics and delivery network. Business growth and lifestyle evolution have contributed to increasing demand for time-sensitive import shipments. Not only in small packages and document scope, but also in handling transportation, logistics and distribution. to analyze how the responsibility of business actors for loss of goods causes consumer losses and causes disputes between business actors and consumers, as well as legal remedies that can be taken when this dispute occurs in the relationship between business actors and consumers. The research method that will be used in this study uses a normative juridical approach. The research specifications are analytical descriptive. The data collection stage is through document studies and interviews. Data analysis is done through qualitative methods. The conclusion drawn from this study is that Article 19 of the UUPK states that if consumers suffer losses in the form of damage, pollution, or financial and health losses due to consuming traded products. Producers as business actors are obligated to provide compensation in the form of refunds, replacement of goods, maintenance, as well as in the form of compensation for compensation made within a maximum period of 7 (seven) days after the date of the transaction. Furthermore, in Article 1367 of the Civil Code it is stated that: